SECONDARY FUNCTIONS OF PERSONAL PRONOUNS IN THE POLISH LANGUAGE - Korpalo, O. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
In the article in comparative aspect reviewed secondary functions of personal pronounsin the Polish language. An important factor in changes in the traditional approaches to the study of the grammatical category of person is the development of functional morphology.